Artistic Image of Luqman Surah with Focus on Educational VersesArtistic Image of Luqman Surah with Focus on Educational VersesArtistic Image of Luqman Surah with Focus on Educational Verses - Mujerlu, Hashem; Ghazanfari, Seyed Akbar; Far, Mohammad Jannati (Journal of History Culture and Art Research, 2017)
Quran is an artful allegory of a scientific-literary text that presents numerous guidelines to achieve perfection and at the same time it shines like a sun in the sky of rhetoric and eloquence. One of the immortal aspects of this divine book is its educational aspect and Luqman Surah is considered one of the prominent ones. The most common method to convey information, persuasion and motivation of audiences in literary work is using artistic images. Suitability for meaning is a condition for the success of artistic image which holy Quran is an outstanding instance of it. In fact, artistic image is a beautiful picture that imagination and emotion breathe the spirit of life in its body. Emphasizing the virtues of words especially stress, pun, rhyme, repetition, redundancy and brevity is a marker of valuing the Quran’s on the issue of education. The use of allegory, light tone, soft rhyme, short, clear and harmonic sentences without any ambiguity is applied in order to understand the issue and persuades and motivates audiences. This study implements discourse analysis by investigating the characteristic of images in Luqman Surah. In this regard, artistic features of Quran and its distinction from other library texts become more evident.